Liver fibrosis assessment: a correlation of fibro scan values with gray scale assessment of portal vein - Pimpalwar, Yayati; Rao, Akhilesh (International Journal of Research in Medical Sciences, 2017)
Background: FibroScan is an expensive modality with excellent accuracy for diagnosis of cirrhosis by measuring liver stiffness. In less developed countries it is not a financially viable method for fibrosis measurement. The aim of this study is to compare and correlate FibroScan values with gray scale sonographic assessment of portal vein calibre diameter which can be done using a basic ultrasonography machine. Methods: Prospective review of 124 patients with chronic liver disease done between Dec 2015 to May 2016 with the objective of correlating FibroScan values with gray scale assessment of portal vein. Results: In our study 50 patients had liver stiffness scores of > or = 7.5 kPa and above. A total of 45 patients had a respiratory phase variation of portal vein calibre of < 20%. Out of these, 37 patients had a liver stiffness score of 7.5 kPa or above. These 37 patients were correctly classified by portal vein calibre variability as having moderate to severe fibrosis. The results of this study revealed a significant correlation (Pearson coefficient, r = -0.617, p= 0.01) between calibre variation of the portal vein and FibroScan scores. We also noted that in presence of mild fibrosis as predicted by lower FibroScan scores, PV calibre variation is not a reliable indicator of mild fibrosis. Conclusions: We propose that, in less developed countries, gray scale assessment of portal vein diameter using any low cost ultrasound machine can be used as an optimal method for predicting moderate to severe liver fibrosis.